2019
DOI: 10.1016/j.msea.2019.01.107
|View full text |Cite
|
Sign up to set email alerts
|

On the role of hydrogen in stress corrosion cracking of magnesium and its alloys: Gas-analysis study

Abstract: One of the main challenges impeding wider uptake of magnesium alloys by the industry is their poor resistance to general corrosion and stress-corrosion cracking (SCC), the nature of which is not fully understood. Although SCC is generally associated with hydrogen embrittlement, the experimental data on the possible hydrogen state, concentration and distribution in Mg is scarce, and its role in SCC is unclear. These issues are addressed in the present study using as-cast technically pure Mg as well as wrought Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 30 publications
5
32
1
5
Order By: Relevance
“…Сравнение с результатами, представленными в [12], показало, что отсутствие внешней нагрузки приводит к увеличению концентрации водорода в сплаве МА14, наиболее ярко проявляющемуся в образцах, с которых не удаляли продукты коррозии. У образцов, с которых продукты коррозии удаляли, этот эффект выражен более слабо.…”
Section: ма14unclassified
See 2 more Smart Citations
“…Сравнение с результатами, представленными в [12], показало, что отсутствие внешней нагрузки приводит к увеличению концентрации водорода в сплаве МА14, наиболее ярко проявляющемуся в образцах, с которых не удаляли продукты коррозии. У образцов, с которых продукты коррозии удаляли, этот эффект выражен более слабо.…”
Section: ма14unclassified
“…Тем не менее оба предположения до недавнего времени не получали достаточно весомых подтверждений. В работах [12][13][14] были проведены комплексные исследования процесса КРН в магниевых сплавах МА14 и МА2-1, а также в чистом магнии, включавшие в себя газовый анализ с определением концентрации водорода в образцах и температур пиков экстракции.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…12 The theory demoatrated that the SCC of the ZK60 and AZ31 alloys was originated from the brittle cracking of the surface hydride film. 13 The study of SCC behavior of AZ80 magnesium alloy in 3.5 wt% NaCl solution demonstrated that SCC behavior was controlled by anodic dissolution. 14 Shervin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen can be immersed between the lattice of the metal and expand or deform the lattice and finally make the metal brittle that is called as hydrogen embrittlement. In the process of rolling, the embrittlement would result in cracks in the middle of the magnesium alloy that affects the quality of the magnesium alloys [31][32][33]. erefore, it is necessary to dehumidify in the rolling environment [34,35].…”
Section: Introductionmentioning
confidence: 99%